Frantic bloom : Anthony Breslin - Breslin, Anthony (Melbourne : Melbourne Books, 2010)
Described as a lovechild of modern primitivism's denouncement of the ultra-technological urban landscape, surrealism's revolt against the tyranny of Reason, and expressionism's desire to externalise the inner turmoil of the individual, Breslin's work is composed of circuitous outlines, undulating curves and Pollock-esque paint splatters, as well as deformed human faces and bold, festive colours.
Keywords: Breslin, Anthony; Graphic arts -- Australia; Australian